(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The article examines the concept of the inner beauty of man from the point of view of Sufi philosophy. The purpose of the study is to determine the essence of inner beauty, its place and importance in spiritual maturation and practical life. The article is based on historical, philosophical, analytical, hermeneutical and interdisciplinary approaches.